Revitalisasi Mushola Al-Karomah Melalui TPA Sebagai Penguatan Moderasi Beragama Masyarakat Dusun Kalibundar - Gunawan Suryo Tirto; Puji Rahayu; Siti Zumrotus Saadah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Mosques play a strategic role as centers of worship and community development at the local level, serving not only as places of worship but also as spaces for non-formal religious education. However, many rural mosques are experiencing declining functionality due to limited facilities, human resources, and a lack of sustainable programs. This condition is evident in the Al-Karomah Mosque in Kalibundar Hamlet, where religious activities have declined due to the lack of sustainability of the Al-Qur'an Education Park (TPA) program. This community service activity aims to revitalize the function of the mosque by strengthening the TPA by emphasizing the instilling of religious moderation values ​​and increasing community participation. The method used is Participatory Action Research (PAR) involving mosque administrators, TPA teachers, community leaders, and parents of students through observation, interviews, and documentation of activities. The program implemented includes improving TPA management, teacher training, developing a simple curriculum based on religious moderation, and reactivating Quran recitation activities and habituating worship. The results of the activity indicate an increase in interest in learning the Quran, strengthening the values ​​of tolerance and togetherness, increasing community participation, and growing awareness of the importance of religious moderation. Thus, revitalizing prayer rooms through strengthening TPA is effective in strengthening religiosity while building social harmony based on religious moderation. The method used in this article is Participatory Action Research (PAR), involving mushola management, TPA teachers, community leaders, and parents of students through field observations, interviews with religious figures, and activity documentation. Program activities include improving TPA management, teacher training, developing a simple curriculum based on religious moderation, and reactivating Qur’anic learning and regular worship activities. The results of the program show: (1) increased interest in learning the Qur'an among children and youth, (2) strengthened values of tolerance, togetherness, and social awareness, (3) growing community participation in religious activities, (4) the role of the mushola as a center of religious moderation at the hamlet level, (5) increased participation of students and community members, (6) rising awareness of the importance of religious moderation, and (7) the reestablishment of Mushola Al-Karomah as a center of community religious activities. Thus, revitalizing the mushola through the TPA has proven effective in strengthening religious values while building social harmony based on religious moderation